2015
DOI: 10.1089/zeb.2014.0999
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Speciation Within the Neotropical CichlidGeophagus brasiliensis(Quoy & Gaimard, 1824) (Teleostei Cichlidae): A New Paradigm in Karyotypical and Molecular Evolution

Abstract: The family Cichlidae is one of the most species-rich taxa in the Neotropics. However, the factors that determine these high levels of biodiversity remain unexplored. We have analyzed the morphological, cytogenetic, and molecular data from 62 specimens of a widespread cichlid, Geophagus brasiliensis, from three adjacent basins in southeastern Brazil. Morphological analyses did not show differences among specimens. The cytogenetic data indicate the occurrence of multiple nucleolar organizer regions and four symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This is also consistent with the study of Melo et al (2021) , who studied patterns of diversification of Characoid fishes, and identified a burst of diversification in Anostomidae, Serrasalmidae and Characidae families. DNA-based species discovery analyses focusing on lower taxonomic units such as genera of cichlids, also discovered multiple divergent evolutionary lineages ( e.g ., Astronotus Swainson, 1839 ( Colatreli et al, 2012 ); Apistogramma Regan, 1913 ( Tougard et al, 2017 ); Gymnogeophagus Miranda-Ribeiro, 1918 ( Říčan et al, 2018 ); Australoheros Říčan & Kullander, 2006 ( Ottoni et al, 2019 ); and Geophagus Heckel, 1840 ( Alves-Silva & Dergam, 2014 ; Carvalho et al, 2018 ; Argolo et al, 2020 )) suggesting cryptic diversity and, possibly, undescribed species.…”
Section: Introductionmentioning
confidence: 99%
“…This is also consistent with the study of Melo et al (2021) , who studied patterns of diversification of Characoid fishes, and identified a burst of diversification in Anostomidae, Serrasalmidae and Characidae families. DNA-based species discovery analyses focusing on lower taxonomic units such as genera of cichlids, also discovered multiple divergent evolutionary lineages ( e.g ., Astronotus Swainson, 1839 ( Colatreli et al, 2012 ); Apistogramma Regan, 1913 ( Tougard et al, 2017 ); Gymnogeophagus Miranda-Ribeiro, 1918 ( Říčan et al, 2018 ); Australoheros Říčan & Kullander, 2006 ( Ottoni et al, 2019 ); and Geophagus Heckel, 1840 ( Alves-Silva & Dergam, 2014 ; Carvalho et al, 2018 ; Argolo et al, 2020 )) suggesting cryptic diversity and, possibly, undescribed species.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the utility of molecular markers in this family to identify the species, better define the genera, and reconstruct their phylogenetic relationships, is well-represented by the huge amount of literature on this topic published in the last 15 years (see Rossi et al, 2016 for a review and Durand et al, 2017 ). In addition, molecular phylogenetic analyses have been used successfully in the investigation of chromosome evolution in some fish groups as those of the genus Characidium ( Pansonato-Alves et al, 2014 ) and Triportheus ( Yano et al, 2014 ), and in Geophagus brasiliensis ( Alves-Silva and Dergam, 2015 ).…”
Section: Introductionmentioning
confidence: 99%